Expert Measurement and Mechanical Combination in Control Reliance Decisions - Libby, Robert; Libby, Patricia A. (The Accounting Review, 1989)
[The ability of Einhorn's [1972] "expert measurement and mechanical combination" to eliminate bias and increase consensus in control reliance decisions was examined. This method uses the human to measure cue values and then combines these component judgments with a mathematical model to form global control reliance decisions. Its aim is to eliminate error induced when the human aggregates information into a global judgment. Two groups of senior auditors evaluated a series of cases by either making global control reliance decisions or making component judgments of the strength of the individual controls and compliance tests. Component judgments of the latter group were combined mechanically into an overall judgment. The mechanically combined component judgments were, on average, more like those provided by a group of firm experts and were more consensual than the global judgments. These results are compared to those of prior studies which examined similar aids.]